Muslims in Myanmar - U Tun Aung, Maulana Akbar Shah; Ushama, Thameem (IIUM Press, 2018)
Muslims of Myamar have been living in the country for more than one thousand years; yet their identities remained unanswered. Their lives are full of challenges and the frequent clashes between them and the Buddhists signify an uncomfortable atmosphere. Their life is an example of identity crisis prevailing in our contemporary world. Currently, their economic life, educational level, social, religious and political status is below the recognized standard. The alarming numbers of poor, jobless, destitute, uneducated, illiterate, refugees and locally displaced Muslims are on the rise. Once the social and moral values are at desperate level, maintaining Islamic identity for the Muslims of Myanmar is unthinkable. Since 2012 Myanmar has shown its desire to participate in democratization whereas many reform activities have taken place. However, the contributions of Muslims are still unacknowledged whether they themselves are inactive or are put aside. The current violence pertaining to Rohingya in the western part of Myanmar highlighted again the ailing episode of Muslims. The violence is seen frequently in Myanmar. It is suggested that the reason of affliction against the Muslims is Islamophobia. This book suggests to the Muslims of Myanmar that they need to solicit the minority status on the basis of religion so as to officially claim the right of minority as well as to enhance their literacy rate and educational standards, particularly in tertiary education by which they can be considered as an indispensable community in the process of democratization of the nation paving the way for ending disputes and see prosperity of the Muslims again.